RETRACTED: Utilization of technogenic waste from energy enterprises - Zvereva Elvira; Safina Gulshat; Ziyatdinov Damir; Zverev Leonid; Lipatov Dmitry (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001